2001
DOI: 10.1523/jneurosci.21-17-06608.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Permeability Transition Pore and Nitric Oxide Synthase Mediate Early Mitochondrial Depolarization in Astrocytes during Oxygen–Glucose Deprivation

Abstract: Recent studies suggest that the degree of mitochondrial dysfunction in cerebral ischemia may be an important determinant of the final extent of tissue injury. Although loss of mitochondrial membrane potential ( m ), one index of mitochondrial dysfunction, has been documented in neurons exposed to ischemic conditions, it is not yet known whether astrocytes, which are relatively resistant to ischemic injury, experience changes in m under similar conditions. To address this, we exposed cortical astrocytes culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 54 publications
11
74
1
Order By: Relevance
“…In our study the astrocytes were able to maintain mitochondrial membrane potential during FC inhibition for 2 h by ATPase reversal in pure cultures but not in the presence of co-cultured neurons (Fig 2 and 6). This is in agreement with previous studies that report the failure of astrocytes to use the compensatory mechanism of ATPase reversal in mixed neuron/astrocyte co-cultures (Reichert et al 2001).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In our study the astrocytes were able to maintain mitochondrial membrane potential during FC inhibition for 2 h by ATPase reversal in pure cultures but not in the presence of co-cultured neurons (Fig 2 and 6). This is in agreement with previous studies that report the failure of astrocytes to use the compensatory mechanism of ATPase reversal in mixed neuron/astrocyte co-cultures (Reichert et al 2001).…”
Section: Discussionsupporting
confidence: 94%
“…The regulatory mechanisms that control preservation of either mitochondrial or plasma membrane potential under the conditions of energy deprivation remain to be investigated. Of note, failure of astrocytes to maintain mitochondrial membrane potential by F 1 F 0 -ATPase reversal when co-cultured with neurons, without changes in astrocytic plasma membrane potential, was also reported by another group in a previous study (Reichert et al 2001). …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Employing intact osteosarcoma cells, Minamikawa et al (46) show a complete reversibility of the MPT without any evidence of cell death. Similarly, it has been reported that astrocytes subjected to oxygen-glucose deprivation showed induction of the MPT without evidence of cell death (47). In this regard, it is noteworthy that our preliminary studies indicate that induction of the MPT in astrocytes when exposed to 100 M manganese acetate for 6 h was completely reversed 48 h after removal of the manganese in the culture medium.…”
Section: Figsupporting
confidence: 88%